Channel-Aware Deep Joint Source-Channel Coding for Multi-Task Oriented Semantic Communication - Wang, Biqi; Gu, Run; Xu, Wei; Jiang, Feng; Li, Mengyu; Wang, Shen (IEEE wireless communications letters, 2025)
Existing deep learning (DL)-based semantic communication generally employs deep neural networks (DNNs) for semantic extraction at a fixed dimension and incorporates channel state information (CSI) to facilitate semantic transmission. However, the optimal dimension of the semantic information to transmit varies with wireless channel conditions, trading off between channel uses and performance depending on the channel condition. To strike the balance, this letter proposes a channel-aware deep joint source-channel coding (CA-DJSCC) for multi-task oriented semantic communication. Specifically, we formulate an optimization problem to characterize the intricate and hard-to-quantify relationship between the channel condition and the optimal dimension. To achieve the channel-adaptive dimension, we develop a joint source and channel encoder, pruning elements based on semantic importance. Correspondingly, we also design a joint source and channel decoder, introducing a reference signal to enhance the multi-task performance. Simulation results demonstrate that the CA-DJSCC achieves superior performance in terms of both image reconstruction and classification tasks, with over 44.1% reduction in average channel uses compared to typical baselines.